Schema-Grounded Agentic AI for Regulatory-Compliant Data Access: Bridging Natural Language and Enterprise Data Governance in Financial Services (International Journal of Research Publications in Engineering, Technology and Management (IJRPETM), 2024)
While many text-to-SQL benchmarks exist in academia, a fundamental tension in enterprise data access using LLM agents remains unaddressed: the system must be powerful enough to synthesise complex query logic that operates on proprietary schemas, yet strict enough to support data governance, access control, and auditability requirements imposed by financial regulators. In this paper, we address this tension through the design and implementation of a schema-grounded multi-agent system called MarketingMind at a Fortune 500 financial services enterprise, benefiting marketing analysts who interact with customer data via an SFMC environment and Google BigQuery. Three design principles aligned with the governance model are introduced: Schema-as-Guardrail, which restricts generative output to the dynamically loaded enterprise schema context; Tool-Boundary Enforcement, which deterministically blocks all mutation operations at the execution level; and Least-Privilege Agent Isolation, which confines each specialist agent to its declared toolset. Evaluation results show 97.3% schema fidelity under grounded conditions, compared with 71.8% in the ungrounded baselines; 100% mutation rejection across 10,000 adversarial inputs; and 0% tool leakage across 5,000 multi-turn sessions. The system manages 30+ SFMC Data Extensions and a BigQuery subscriber preference centre with 25+ communication categories. Findings highlight the need to treat governance as an architectural primitive and to complement prompt instructions with deterministic enforcement mechanisms when deploying enterprise LLMs in compliance-sensitive areas.
Keywords: agentic AI; text-to-SQL; data governance; large language models; financial services compliance; schema grounding; multi-agent systems; access control; Salesforce Marketing Cloud; BigQuery; retrieval-augmented generation; enterprise AI deployment